Polycythemia: A Clinical Approach - Cahyanur, Rahmat; Rinaldi, Ikhwan (UI Scholars Hub, 2019)
Polycythemia or erythrocytosis is an increase in the number of red blood cells in circulation marked by the increase in hematocrit. Polycythemia is a case that still raises questions and dilemma for doctors. In this paper, it will be discussed about the diagnostic approach and management of polycythemia. The initial complaints of polycythemia are generally nonspecific, such as weakness and dizziness due to blood hyperviscosity. It is also essential to know accompanying diseases, routine medications, habits, and family histories of the patients. Patients with polycythemia commonly exhibit plethora. In vital sign examination, hypertension can be found in polycythemia vera. In general examination, we should look for signs that lead to secondary polycythemia, such as low oxygen saturation that can be found in secondary polycythemia. Initial workup that should be done is a complete blood count. Ferritin and transferrin saturation are evaluated to assess the iron status that can disguise the incidence of polycythemia, especially when the image of the blood smear indicates a microcytic hyperchromic. Advanced work up that can be done is genetic examination. In the case of polycythemia vera, the primary purpose of treatment is to prevent thrombotic events. In the case of secondary polycythemia, the aim of management is to identify the underlying disease and treat it, which one of them is phlebotomy.